PENGARUH LUAS LAHAN, BIAYA PRODUKSI, DAN JUMLAH PRODUKSI TERHADAP PENDAPATAN USAHATANI JERUK (Citrus sinensis) DI DESA TUNGKU JAYA KECAMATAN SOSOH BUAY RAYAP KABUPATEN OGAN KOMERING ULU - Endang Lastinawati; Sa’diah, Iis; Ayu Ogari, Putri; Chuzaimah; Swasdiningrum Putri, Trisna Wahyu (Jurnal AGRIBIS, 2025)
Orange is one of the superior fruits that is widely developed in Indonesia. This study aims to calculate the income of orange farming and analyze the effect of land area, production costs, and production volume on orange farming income. The study was conducted in Tungku Jaya Village, which is one of the orange production centers in Ogan Komering Ulu (OKU) Regency. The research method used was the survey method. Farmer samples were taken using a simple random method, as many as 30 farmers from 50 orange farmers in the research location. The data were processed using a mathematical formula for income, and multiple linear regression methods. The results showed that the income of orange farming in Tungku Jaya Village, Sosoh Buay Rayap District was IDR 12,874,012.71/ha/year. The income of orange farming in Tungku Jaya Village was influenced by the amount of production and production costs. While the area of ​​land had no significant effect on orange farming income.